Esthetic improvement using maxillary immediate denture and mandibular overdenture - Finka Nur Ikhwani; Vera Aryanti; Setyawan Bonifacius; Rasmi Rikmasari (Indonesian Journal of Prosthodontic, 2023)
Loss of teeth in adult needs to be replaced with dentures to restore masticatory and esthetic functions. Dentures are made immediately before extraction and used immediately after extraction, so that they do not change in appearance or function. If patient has restorable teeth, the teeth can be used as denture support. Overdentures supported by one or more restored teeth or implants as periodontal and mucosal support to improve durability of the denture. This arti-cle discusss maxillary immediate denture and mandibular overdenture on a woman who felt uncomfortable with the denture that has been used for 4 years. Patient wants a new denture without changing appearance. Intraoral exa-mination found tooth 17, 16, 26 GIC fillings, 13 dowel crown, 31, 32 PFM crowns, 42 composite filling with mobili-ty grade I, and 44 caries. This case was managed with extraction teeth 16, RCT 26, and extraction 13 before insert-ion the maxillary immediate denture with cusil #17 and overdenture 26, and also RCT was performed on 44, 42, 32, 31 followed by insertion the magnetic overdenture 44, 42 and metal coping overdenture 31, 32. It is concluded that immediate denture and overdenture provide optimal results for esthetic improvement and patient satisfaction.